2021
DOI: 10.1002/onco.13678
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib and Panitumumab for RAS Wild-Type Metastatic Colorectal Cancer

Abstract: Lessons Learned Antitumor activity was observed in the study population. Dose modifications of cabozantinib improve long‐term tolerability. Biomarkers are needed to identify patient populations most likely to benefit. Further study of cabozantinib with or without panitumumab in patients with metastatic colorectal cancer is warranted. Background The epidermal growth factor receptor (EGFR) antibody panitumumab is active in patients with RAS wild‐type (WT) metastatic colorectal cancer (mCRC), but nearly all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Five studies reported outcomes in patients with gastrointestinal cancers, including three that showed encouraging clinical activity with: cabozantinib in combination with either nivolumab or durvalumab in patients with HCC; cabozantinib plus durvalumab in patients with advanced GEA and CRC; and cabozantinib plus panitumumab in patients with mCRC. 32 , 67 , 69 , 71 , 73 , 74 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies reported outcomes in patients with gastrointestinal cancers, including three that showed encouraging clinical activity with: cabozantinib in combination with either nivolumab or durvalumab in patients with HCC; cabozantinib plus durvalumab in patients with advanced GEA and CRC; and cabozantinib plus panitumumab in patients with mCRC. 32 , 67 , 69 , 71 , 73 , 74 …”
Section: Resultsmentioning
confidence: 99%
“…In a phase Ib study of 25 patients with chemotherapy refractory KRAS wild-type mCRC, outcomes were measured after treatment with cabozantinib (60 mg/day) and panitumumab. 32 , 69 Median (95% CI) OS and PFS were 12.1 (7.5–14.3) months and 3.7 (2.3–7.1) months, respectively. Of the 25 patients treated, 13 had received prior anti-epidermal growth factor receptor (anti-EGFR) therapy, and four patients (16%) had a confirmed PR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cabozantinib interferes with AXL signaling, downregulates EMT-TFs, and increases E-cadherin expression. However, in a combined treatment with the EGFR inhibitor panitumumab for KRAS wild-type CRC patients, cabozantinib showed a 16% response in terms of clinical parameters (84). Methotrexate successfully increased Ecadherin expression levels 10-fold in CRC cell lines, and it has been shown to be ineffective in clinical settings (85).…”
Section: Emt Components As Targets To Inhibit Metastasismentioning
confidence: 99%